Analytical calculations of the angles of rotational transform specified by different plasma pressure profiles and an external transverse magnetic field in the torsatron - Kuznetsov, Yu.К.; Pinos, I.B.; Tyupa, V.I. (Вопросы атомной науки и техники, 2003)
The authors of the present work have calculated the angles specified by various plasma pressure profiles depending on the parameter α that characterizes the profile of vacuum angles of rotation angles and on the magnetic axis displacement caused by an external transverse magnetic field. The authors have considered three laws of plasma pressure distribution over vacuum magnetic surfaces: P₁=P₀, P₂=P₀(1-y(r)/y(r₀)); Р₃=Р₀(1-y(r)/y(r₀))². The calculations showed, that in the case of magnetic axis shifting into the inside of the torus and at low values of α, the rotational transformation angle of a torsatron decreases up to zero with plasma pressure increasing. In this case, the splitting of magnetic surfaces caused by pressure distributions Р₃=Р₀(1-y(r)/y(r₀))² takes place in the central region of a magnetic configuration. As plasma pressure distributed by the law P₁=P₀ increase the splitting of magnetic surfaces due to the helical winding perturbation only occurs.